1994
DOI: 10.1051/agro:19940305
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the height and angles of orientation of the upper leaves in the maize canopy using stereovision

Abstract: Summary -3D models of vegetation have been constructed to allow various simulations, such as the interception of incoming radiation, radiative transfer, reflectance simulation in remote sensing, study of plant function, and interspecies competition. The construction of such 3-D models is based upon simple geometric assumptions and several production rules (eg, growing, branching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…We open this discussion with a review of previous measurement techniques used to describe the geometry of grasses, beginning with the methodology presented by Bonhomme and Varletgrancher (1978 More recently, Biskup et al (2007) developed their own stereo imaging system and showed its applicability by digitizing the upper layer soybean canopy leaves covering an area of 1.20 by 0.80 meter. The idea is similar to that of Ivanov et al (1994), where two photographs from the canopy are simultaneously taken and corresponding points on each picture are matched, allowing the estimation of their coordinates. The great improvement introduced by this technique is the automatic marking and matching of points, which greatly hastens the process of digitally constructing the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We open this discussion with a review of previous measurement techniques used to describe the geometry of grasses, beginning with the methodology presented by Bonhomme and Varletgrancher (1978 More recently, Biskup et al (2007) developed their own stereo imaging system and showed its applicability by digitizing the upper layer soybean canopy leaves covering an area of 1.20 by 0.80 meter. The idea is similar to that of Ivanov et al (1994), where two photographs from the canopy are simultaneously taken and corresponding points on each picture are matched, allowing the estimation of their coordinates. The great improvement introduced by this technique is the automatic marking and matching of points, which greatly hastens the process of digitally constructing the plant.…”
Section: Introductionmentioning
confidence: 99%
“…As the distance between cameras is known, the positions of the points can be calculated from the rectified images. The rectification process depends on parameters that are unique to the photography setup and that are determined through calibration Ivanov et al (1994). describe an application of stereo-photography in the reconstruction of a maize canopy.…”
mentioning
confidence: 99%
“…Kise and Zhang (2008) used a stereo system for crop rows detection. Ivanov et al (1994) applied stereo vision to study the leaf angle and area in a maize canopy. Müller-Linow et al (2015) have tested stereo-imaging on sugar beet in natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic tracking instrument is a kind of digital measuring tools based on electromagnetism [3]. It is an effective tool of getting structure data of fruit trees because it is not only an easy-to-use, extremely accurate and broad action sphere device but also a powerful survey tool which can track the space track and calculate the inclination angle of stylus [2].…”
Section: Introductionmentioning
confidence: 99%